Qualidade microbiológica, físico-química e perfil eletroforético de amostras de soros de queijo produzidos no norte de Minas Gerais - Livia Carolina Leite Duraes (2017)
Cheese, by volume of production, is the main lactic derivative produced in Brazil. During its production, a serum release occurs, which is still considered a by-product of the cheese industry. Cheese serum is important from a nutritional, functional and biological point of view, however, researches with this by-product are still scarce. Therefore, the objective of this work is to evaluate the chemical substance of milk from the semi-arid region of northern Minas Gerais, as physical and chemical characteristics of sera of different types of cheeses, which are collected in a dairy industry of Montes Claros / MG, aiming at their use in the elaboration of new food products. For the analyzes, samples of raw milk were collected from the farms of the routes in which the dairy collected, samples of pasteurized milk used in each production of the cheeses under study in the same quantity and day of the collections of the serum, 3 samples of serum of Minas type cheese Standard, 5 serum samples of mozzarella cheese and 5 serum samples of Prato cheese. Samples from different production lots were collected between January and March 2016. All samples of raw milk were analyzed in their chemical composition, by analysis of fat, protein, total dry extract, dry extract defatted, determination of the acidity in degrees Dornic, determination of density at 15 ° C, fat, total dry extract, dry extract defatted, proteins, moisture and ashes. The electrophoretic profile of the proteins of the three serum types was obtained using the SDS-PAGE technique. In relation to the physical-chemical analyzes, the three types of cheese whey analyzed did not differ significantly with each other, with the exception of the acid values and are within the results obtained in the literature and within the rights required by the legislation. The electrophoretic profile makes possible the publication and indication of the proteins present in the sera, besides allowing an observation of uniformity among protein bands, suggesting that the protein profile does not differ between the types of cheese sera studied. In relation to microbiological analyzes, all samples analyzed were in accordance with current legislation. With this, one can use the three types of whey studied without loss of its main characteristics for a manufacture of dairy drinks.